Trauma care facilities in selected hospitals in the Western Province : Classification according to the proposed trauma care expectation matrix and the opinions of first contact medical officers regarding available facilities and training - Fernando, E (My University, 2009)
Three hundred first contact medical officers were also included in the study. A check list developed based on the required facilities included under eight of the nine "domains" relevant to trauma care, as specified in the TCEM according to proposed four levels of trauma centers. Consisted of an interviewer administered questionnaire which included selected socio demographic characteristics , data pertaining to training and level of satisfaction regarding availability of facilities and training received. The available facilities was assessed separately for the NHSL and other health care institutions grouped into h hospital categories according to the new scheme of categorization adopted by the Ministry of Health recently. Then the available I facilities were compared with the four levels of trauma care centers as described according to the TCEM. The continuous data were expressed as means and SD and the chi squared test was applied to test for associations between " overall satisfaction" and relevant demographic and service related variable